2016
DOI: 10.1108/scm-07-2015-0283
|View full text |Cite
|
Sign up to set email alerts
|

Motivational influences on supply manager environmental sustainability behavior

Abstract: Purpose Although supply chain managers serve a central role when implementing corporate environmental sustainability objectives, existing literature does not demonstrate high levels of supply manager support for such initiatives. This paper aims to investigate the potential of individual behavioral influences to explain supply manager orientation toward environmental responsibility. Methodology/approach This paper constructs a research model based on the theory of planned behavior (TPB) to explore how person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 104 publications
1
11
0
Order By: Relevance
“…TPB considers that the influence of the environment will stimulate individuals to generate intentions and behavior. Various studies in sustainability field have also found the same thing where social influences will drive sustainable behavior (Heeren et al 2016;Swaim et al 2016;Giampietri, Finco, & Giudice 2016). However, the findings of this study are in line with Yadav & Pathak (2016) who found no influence from the environment on sustainable behavior.…”
Section: Resultssupporting
confidence: 82%
“…TPB considers that the influence of the environment will stimulate individuals to generate intentions and behavior. Various studies in sustainability field have also found the same thing where social influences will drive sustainable behavior (Heeren et al 2016;Swaim et al 2016;Giampietri, Finco, & Giudice 2016). However, the findings of this study are in line with Yadav & Pathak (2016) who found no influence from the environment on sustainable behavior.…”
Section: Resultssupporting
confidence: 82%
“…Several previous studies have widely suggested the extent to which the personal characteristics of leaders are translated into a professional ethic that aims to translate personal values into corporate vision, to achieve corporate excellence (Gadenne & Mckeiver, 2009; Rivera, 2019). The personal commitment of the manager, owner, or founder is related to environmental practices such as GSCI (Anthony Swaim et al, 2016; Fraj et al, 2013). Leader support for environmental protection is positively related to employees' willingness to become involved in eco‐initiatives and green internal integration (Ramus & Steger, 2000; Sarkis et al, 2010).…”
Section: Theory Foundation and Hypothesesmentioning
confidence: 99%
“…To our knowledge, this is one of the first studies to thoroughly consider the firm-level empirical verification of game theory model results to explore and discuss RDM's effects. These findings can offer meaningful insights into sustainable development strategies by retailers' RDM, thus expanding previous scholars' research on sustainability (Nguyen et al, 2023;Swaim et al, 2016;Wijethilake, 2017).…”
Section: Theoretical Implicationsmentioning
confidence: 53%
“…These existing literatures have studied the impact of rational (irrational) decision-making by managers. Based on these literature streams, we also find that rational and irrational behavior decisions by managers have a significant impact on production decisions and environmental sustainability, such as Swaim et al (2016), da Silva et al (2020), and Yang et al (2022. This research contributes to the extensive body of literature concerning decision rationality.…”
Section: Behavioral Decision-making and Environmental Impactmentioning
confidence: 61%
See 1 more Smart Citation